Single-crystal growth of a FeCoCrMnAl high-entropy alloy. Issue 2 (4th March 2017) - Feuerbacher, M.; Würtz, E.; Kovács, A.; Thomas, C.
ABSTRACT: We report on single-crystal growth of the equiatomic FeCoCrMnAl high-entropy alloy by means of the Bridgman technique. Our crystals are about 1 cm in diameter and 6.6 cm in length. X-ray Laue images taken at various positions on their surface are sharp and mutually consistent. The material has a microstructure consisting of B2 inclusions in a body-centred cubic matrix. The inclusions are {0 0 1} platelets of about 65 nm thickness with varying lateral extensions of the order of 500 nm, predominantly containing Al and Co. The matrix is rich in Fe and Cr. GRAPHICAL ABSTRACT: IMPACT STATEMENT We report the growth of a cubic-centimetre-sized single crystal of a high-entropy alloy. We characterize a Bridgman crystal of the equiatomic FeCoCrMnAl phase and analyse its two-phase structure.